Laser printing of micro-electronic communication systems for smart implants applications - Moura, Caroline Gomes (2020)
Endow the implant with intrinsic communication system between sensors and actuators or between implant and patient is a key factor for its long-term success. The capacity of early diagnosis of failures and the ability to remedy them are necessary to minimize expensive complications and reducing revision procedures. Ti6Al4V is the most used titanium alloy for implant’s fabrication. In this sense, this work presents a promising approach to print communication systems by using laser technology, aiming integrate the smart components on titanium implants. Laser has been employed as a versatile tool to modify the surface in different ways, such as texturing, oxidizing and sintering. Silver wires have been printed on Ti6Al4V surface in order to conduct electrical current. To minimize current loss for the substrate, titanium oxide layer has been produced by different methods (laser and anodization). Laser sintering (LS) has been also compared to a conventional method (Hot-pressing- HP) to consolidate the silver powder into the cavities. In comparison to the conventional techniques, laser demonstrated to be a competitive approach to oxidizing the surface and also for consolidating the micro-wires on Ti6Al4V surface. Consequently, the micro-wires printed by laser approach presented satisfactory results in terms of electrical resistance, actuating as the conductor path for electrical current, with values of 0.0131 Ω, which is similar to the resistance of the wire printed in an insulator substrate.